Proteolytic Activity of The Entomopathogenic Fungi (Penicillium sp. ) of Cockroaches (Periplaneta americana) - Ahmad Ikhsanudin; Emantis Rosa; Christina Nugroho Ekowati (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2019)
Cockroaches (Periplaneta americana) were the insect vectors of disease that caused adverse effects on human health. Control cockroch excessive use of insecticides can lead to residus in the environment and resistance cockroach. Therefore it was necessary to use an alternatives such as such as entomopathogenic fungal as biologycal agents. The entomopathogenic fungi penetrated via the integument of an cockroach to reach the hemocoel. Proteins were the molecules responsible for integument strength in cockroach, It was synthesis the proteases to degrading proteins. The study begins with the isolation of entomopathogenic fungi using the moist chamber method with cockroach as insect bait. Fungus that grow on cockroches are cultured and purifed on Potato Dextrose Agar (PDA) medium then identified. Identification was carried out through macroscopic observations including colony color and diameter and microscopic observations including conidia, conidiophores, hyphae, vesicles, fialids, and leg cells. The result of isolation and identification obtained as Penicillium sp. Proteases enzimatic activity tested on PDA with anlene 1%. The clear zone formed is measured to show the activity of proteases produced by Penicillium sp.